2006
DOI: 10.2460/ajvr.67.7.1140
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of antimicrobial transfer from treated to untreated mammary gland quarters by use of high-pressure liquid chromatography for detection of cloxacillin in milk samples from nonlactating dairy cows

Abstract: Within-cow half-udder comparison trials are valid for antimicrobial trials in nonlactating cows, although transfer of antimicrobials does occur in trace concentrations. Ipsilateral or diagonal-contralateral treatment designs perform similarly. This type of design is economical for researchers, although care must be taken to account for within-cow clustering of mammary gland quarter data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…This study also investigated the concentrations of antibiotic in quarters, and whether selection of ipsilateral versus diagonalcontralateral quarters for treatment affected cloxacillin transfer among quarters. Cloxacillin was detected in 25% of all untreated mammary gland quarters (Sanford et al, 2006a), but concentrations of cloxacillin in untreated quarters were below MIC for targeted mastitis pathogens. Their study also found significant differences in cloxacillin concentrations in the ipsilateral or diagonal treatment groups.…”
Section: Between-quarter Interdependence Within Cowsmentioning
confidence: 95%
See 3 more Smart Citations
“…This study also investigated the concentrations of antibiotic in quarters, and whether selection of ipsilateral versus diagonalcontralateral quarters for treatment affected cloxacillin transfer among quarters. Cloxacillin was detected in 25% of all untreated mammary gland quarters (Sanford et al, 2006a), but concentrations of cloxacillin in untreated quarters were below MIC for targeted mastitis pathogens. Their study also found significant differences in cloxacillin concentrations in the ipsilateral or diagonal treatment groups.…”
Section: Between-quarter Interdependence Within Cowsmentioning
confidence: 95%
“…Their study also found significant differences in cloxacillin concentrations in the ipsilateral or diagonal treatment groups. The results of their study suggest that within-cow half-udder comparison trials are valid for antimicrobial trials in nonlactating cows, although transfer of antimicrobials does occur in trace concentrations (Sanford et al, 2006a).…”
Section: Between-quarter Interdependence Within Cowsmentioning
confidence: 97%
See 2 more Smart Citations
“…However, because the cloxacillin and cloxacillin benzathine (1:1) concentrations diminish with each milking, this seems unlikely. These concentrations might also be attributed to carry-over effects as observed by Sanford et al [ 45 ]. These authors found cloxacillin residues in 25% of untreated udder quarters located ipsilaterally or diagonally to quarters treated with cloxacillin DCT.…”
Section: Discussionmentioning
confidence: 87%